The Effect of Modified Audit Opinions on Share Prices In Casablanca Stock Exchange - Amine EL BADLAOUI; Mariam CHERQAOUI (Communications of International Proceedings, 2022)
This study aims at investigating the stock market reaction in Morocco to the release of modified audit opinions (Qualified audit opinions and unqualified audit opinions with explanatory notes). We use the event study methodology, using a long event period (-20 days; +20 days) to test whether there are significant abnormal returns on share prices after the release of modified audit reports of listed companies in the Casablanca Stock Exchange (CSE) during the period 2010-2019. The results of our study show that there is a negative market reaction during the event period, but this reaction is not significant, meaning that Moroccan investors do not consider the auditor's opinion to be relevant for their investment decisions. Based on the conclusions of this study, the researchers recommend the use of alternative event and estimation periods. Second, it is recommended that more research on this topic be conducted in developing markets, since they always result in mixed and inconsistent results, unlike developed markets. Third, developing financial markets are characterized by the existence of a small number of listed companies, so it is necessary to extend the years of study in order to have a larger number of observations.
Keywords: Market reaction; Audit reports; Casablanca Stock Exchange; Modified audit reports; Qualified audit reports; Unqualified audit reports with explanatory notes; Event Study Methodology.